2019
DOI: 10.4236/jep.2019.104029
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Chemical Forms in Two Calcareous Soils Treated with Different Levels of Incubation Time and Moisture Regimes

Abstract: Sequential extraction is used effectively to determine the chemical forms of heavy metals. Since few studies have been conducted in calcareous soils of Iran, the current research has been carried out to evaluate the effect of moisture regimes and incubation time on the chemical forms of cadmium in two calcareous soils. Treatments included three levels of cadmium (0, 30 and 60 mg/kg of soil as CdSo 4), three incubation times (2, 4 and 8 weeks), two soils (clay and sandy clay loam) and two moisture regimes (Wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 30 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…All soil amendments increased Cd accumulation by shoots and roots in jatropha and acacia by factors of up to 1.3 to 1.7 and 1.0 to 1.7, respectively. Cadmium levels in soil, on the other hand, have been demonstrated to increase with time as a result of increased sorption of Cd on OM 23 . Studies have also demonstrated that jatropha can serve as an accumulator for a variety of heavy metals; however, it is not a suitable accumulator for all heavy metals as it accumulates some at only very low quantities in shoots.…”
Section: Resultsmentioning
confidence: 99%
“…All soil amendments increased Cd accumulation by shoots and roots in jatropha and acacia by factors of up to 1.3 to 1.7 and 1.0 to 1.7, respectively. Cadmium levels in soil, on the other hand, have been demonstrated to increase with time as a result of increased sorption of Cd on OM 23 . Studies have also demonstrated that jatropha can serve as an accumulator for a variety of heavy metals; however, it is not a suitable accumulator for all heavy metals as it accumulates some at only very low quantities in shoots.…”
Section: Resultsmentioning
confidence: 99%
“…22,[33][34][35][36] Long-term accumulation of Cd in soil can pose a risk to the food chain and human health. [37][38][39][40][41] Studies have shown that Cd adsorbs onto MPs, and its uptake and accumulation can impact nutrient delivery. 42,43 PS is an aromatic polymer commonly used in various products, including CDs, toys, toothbrushes, and styrofoam.…”
Section: Mps Have Been Shown To Affect Plants In the Environment By A...mentioning
confidence: 99%
“…Cadmium (Cd) is a highly toxic element that can contaminate soil through various sources, such as aerial deposition, irrigation, fertilizers, pesticides, and industrial waste 22,33–36 . Long‐term accumulation of Cd in soil can pose a risk to the food chain and human health 37–41 . Studies have shown that Cd adsorbs onto MPs, and its uptake and accumulation can impact nutrient delivery 42,43 .…”
Section: Introductionmentioning
confidence: 99%
“…Temperatures in the climate vary (the mean monthly maximum ranges from 6.30°C to 29.50°C), and November to May is when most rain falls (346 mm on average). The terms xeric and thermic refer to the soil's warmth and moisture (Rassaei et al, 2019a). This region's geology is evidenced by lucostrin deposits, calcareous marls, and gypsiferous marls.…”
Section: Area Descriptionmentioning
confidence: 99%
“…Sequential extraction is employed effectively to work out the chemical types of heavy metals. By using the extractants which boosts from low acidic extraction solution to high acidic extraction solution we will have some data about the bioavailability of metals and their association with soil components (Rassaei et al, 2019a). One of the most important factors in increasing the yield production is phosphorus fertilizer.…”
Section: Introductionmentioning
confidence: 99%